Enhanced transient receptor potential channel‐mediated Ca2+ influx in the cells with phospholipase C‐δ1 overexpression: its possible role in coronary artery spasm. (16th February 2017) - Murakami, Kazuo; Osanai, Tomohiro; Tanaka, Makoto; Nishizaki, Kimitaka; Kinjo, Takahiko; Tanno, Tomohiro; Ishida, Yuji; Suzuki, Akiko; Endo, Tomohide; Tomita, Hirofumi; Okumura, Ken
Abstract: We reported that coronary spasm was induced in the transgenic mice with the increased phospholipase C (PLC)‐δ1 activity. We investigated the effect of enhanced PLC‐δ1 on Ca 2+ influx and its underlying mechanisms. We used human embryonic kidney (HEK)‐293 and coronary arteries smooth muscle cells (CASMC). Intracellular free Ca 2+ concentration ([Ca 2+ ]i ; nm ) was measured by fura‐2, and Ca 2+ influx was evaluated by the increase in [Ca 2+ ]i after addition of extracellular Ca 2+ . Acetylcholine (ACh) was used to induce Ca 2+ influx. ACh‐induced peak Ca 2+ influx was 19 ± 3 in control HEK‐293 cells and 71 ± 8 in the cells with PLC‐δ1 overexpression ( P < 0.05 between two groups). Nifedipine partially suppressed this Ca 2+ influx, whereas either 2‐APB or knockdown of classical transient receptor potential channel 6 (TRPC6) blocked this Ca 2+ influx. In the human CASMC, ACh‐induced peak Ca 2+ influx was 29 ± 6 in the control and was increased to 45 ± 16 by PLC‐δ1 overexpression ( P < 0.05). Like HEK‐293 cells, pretreatment with nifedipine partially suppressed Ca 2+ influx, whereas either 2‐APB or knockdown of TRPC6 blocked it. ACh‐induced Ca 2+ influx was enhanced by PLC‐δ1 overexpression, and was blocked partially by nifedipine and completely by 2‐APB. TRPC‐mediated Ca 2+ influx may be related to the enhanced Ca 2+ influx in PLC‐δ1 overexpression.